Dictionary of Filipino culture and values - Andres, Tomas D. (Giraffe Books, 1994)
It aims to make readers see the practical wisdom inherent in the Filipino indigenous cultural and philosophical traditions reflected in Filipino values, and will be able to identify the practical wisdom and articulate the significance and positiveness of the Filipino values operative in his life. Intended for all Filipinos and all those who sympathize with Filipinos as a reference book for their lives, studies and courses.